Species lists of birds - Unidentified author (Colorado State University. Libraries, 2007)
Working list of birds used by the SGS-LTER Program on the Central Plains Experimental Range, Nunn, Colorado.
Keywords: shortgrass steppe; long term ecological research; grassland ecology; Pawnee National Grassland; Central Plains Experimental Range